The Effect of the Combination of Counseling and Dhikr Interventions: Self-Acceptance of the Elderly in Nursing Home - Minarti Minarti; Kastubi Kastubi; N Fadilah; Fathimath Shifaza (International Journal of Advanced Health Science and Technology, 2022)
Individuals who become elderly will experience physical changes from their initial body condition to being very weak. The declining conditions experienced by the elderly tend to cause physical and psychological health problems and dissatisfaction in life. The purpose of this study is to analyze counseling and dhikr intervention on the attitude of self-acceptance of the elderly. An experimental design using pre-test and post-test control groups was conducted among 30 elderly people living in nursing homes with the inclusion criteria of being able to communicate well, not deaf, not cognitively impaired, or depressed. Participants were randomly allocated, to the intervention group at Nursing Home of Jambangan and the control group at Nursing Home of Hargo Dedali in Surabaya Indonesia. Measurement of self-acceptance was carried out twice through a questionnaire, namely before the counseling and dhikr intervention and 8 weeks after. Data were analyzed using paired t-test. The results showed that there is pre-post differences in the group that received counseling and dhikr intervention (p-value = 0.000). The participants in the intervention group showed an increase in self-acceptance while in the control group there is no significant difference with a p-value of 0.937. Religious support for dhikr and counseling needs to be carried out intensively for the elderly as religious activities can provide a sense of peace, surrender, and surrender to Allah Almighty. The combination of counseling and dhikr is an effort to improve oneself spiritually and has a positive correlation with the attitude of self-acceptance of the elderly living in nursing homes. Institutions where services for the elderly can contribute to the elderly living in nursing homes by carrying out programmatic activities, namely counseling, especially for the elderly who have just entered special institutions for the elderly, spiritual approaches also need to be improved both in groups and individuals such as prayer, dhikr, and worship. others according to ability. A very important contribution is the guidance carried out by cleric so that elderly worship is more focused. This is an effort so that the elderly can accept the conditions they are facing and can accept themselves living in the orphanage.